EFISIENSI DAN EFEKTIFITAS PARTISIPASI ANGGARAN PADA SKPD DINAS PERTANIAN DAN PANGAN KABUPATEN MAGELANG - Lisnawati, Lisnawati; Priyono, Nuwun (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
This study aims to analyze the effectiveness and efficiency of the implementation of the expenditure budget Dinas Pertanian dan Pangan Kabupaten Magelang. This research uses qualitative research by using a descriptive approach. The level and effectiveness criteria of the implementation of the expenditure budget in the Dinas Pertanian dan Pangan Kabupaten Magelang in 2016-2019 varied greatly, the highest level of effectiveness occurred in 2018 and the lowest in 2016. The implementation of the budget for 2017, 2018 and 2019 was said to be effective, but in 2016 the level of effectiveness is still very lacking because the realization of the budget has a difference that is still very far from the target budget. This difference occurs because of a policy in 2016 that Dinas Pertanian dan Pangan Kabupaten Magelang does not implement grants. Dinas Pertanian dan Pangan Kota Magelang assesses that when the programmed activities are realized and as expected, the activities are said to be effective. The implementation of the 2016-2019 Dinas Pertanian dan Pangan direct expenditure budget as a whole has been processed efficiently. The implementation of the direct expenditure budget for 2017-2019 is categorized as very efficient. Only in 2016 was considered quite efficient. Managing direct budget has met the efficiency requirements, namely the use of minimum funds to achieve maximum results